Lower gastrointestinal malignancies - Ben-Josef, Edgar; Koong, Albert (Radiation medicine rounds, 2010)
Lower Gastrointestinal Malignancies. This issue of Radiation Medicine Rounds focuses on lower gastrointestinal malignancies. The American Cancer Society estimates that in 2009 there were a total of 152,000 new cases of colorectal and anal cancers diagnosed with over 50,000 deaths from these cancers. Thus it is crucial for the practitioner to be up-to-date onthe latest insights regarding their management. Included are chapters on the evolution of systemic agents,neoadjuvant treatment, radiation therapy, chemoradiation therapy, rectal cancer and anal cancer covering the vast majority of these tu.